RISK MANAGEMENT IN PUBLIC-PRIVATE PARTNERSHIP AND OTHER MAJOR INFRASTRUCTURE PROJECTS. Issue 6 (3rd June 2021) - Sidorenko, Alex; Kilinkarov, Vladimir; Belkov, Alexey
ABSTRACT: Any public infrastructure project, and especially a public–private partnership (PPP) project, is a complex project with many different obligations. It weaves together the interests of a wide range of participants: public and private partners, governmental authorities, and public organizations, the private partner's shareholders, banks, and other financing entities, contractors, suppliers, operators, and insurers, as well as the interests of third parties such as consumers, and public organizations affected by the project in one way or another.These circumstances predetermine the large number of risks the private and public partners face in implementing a project, including construction and operating risks, tax, financial, market, political, legal, information, and other risks.Many of these risks are manageable and can be prevented or identified at the stage when they can be kept from materializing and resulting in specific adverse consequences such as breach of obligations and, in the worst-case scenario, default on the project. Both the private and the public partner should consider and control these risks. Proper risk management is also an important factor in reaping financial and operating benefits.The article's objective is to promote modern approaches to risk analysis and risk-oriented decision-making when implementing PPP projects.